Pre-service science teacher’s opinions on virtual labs and their use in biology - Koca Asiye Bilge; Kizilay Esra (Research on Education and Media)
This study sought to investigate pre-service science teachers’ opinions about using virtual laboratories and virtual laboratories for biology. The study group of the research consisted of four pre-service science teachers (two girls and two boys) who had virtual laboratory experience by taking at least one of the courses related to technology integration at a state university located in the Central Anatolia region in Türkiye. The research used a semi-structured interview form with open-ended questions, a common data collection method in qualitative research. The data were examined using the content analysis method. The usage of virtual laboratories in science lectures in terms of the teacher, student, and educational processes was mentioned by pre-service science teachers. Pre-service teachers claim that virtual laboratories help students gain experience and strengthen their critical thinking and research skills. According to pre-service teachers, biology, cells, and the study of onion skin and bacteria are only a few examples of virtual laboratory applications that can be used in science teaching. They emphasized that it included biology-related themes, offered opportunities for lab work, dispelled misconceptions, and allowed students to use a microscope.